2015
DOI: 10.1007/s11270-015-2529-9
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic and Lead Uptake by Vegetable Crops Grown on an Old Orchard Site Amended with Compost

Abstract: The potential for lead (Pb) and arsenic (As) transfer into vegetables was studied on old orchard land contaminated by lead arsenate pesticides. Root (carrot), leafy (lettuce), and vegetable fruits (green bean, tomato) were grown on seven “miniplots” with soil concentrations ranging from near background to ≈ 800 and ≈ 200 mg kg−1 of total Pb and As, respectively. Each miniplot was divided into sub-plots and amended with 0% (control), 5% and 10% (by weight) compost and cropped for 3 years. Edible portions of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 30 publications
5
24
1
1
Order By: Relevance
“…Arsenic has been reported to accumulate in the edible parts of different plant species (Li et al, 2016). McBride et al (2015) also found a significant accumulation of As in carrot, lettuce, green bean ( Phaseolus vulgaris L.), and tomato; however, the tested concentrations were much higher than those measured in our studied substrates. Rosas‐Castor et al (2014) observed As accumulation in maize ( Zea mays L.) when grown on a soil with an As concentration comparable with that in our substrates, but their recorded values in the shoot were mainly below our LQ for As (1.24 mg kg −1 , Supplemental Table S1).…”
Section: Resultscontrasting
confidence: 52%
“…Arsenic has been reported to accumulate in the edible parts of different plant species (Li et al, 2016). McBride et al (2015) also found a significant accumulation of As in carrot, lettuce, green bean ( Phaseolus vulgaris L.), and tomato; however, the tested concentrations were much higher than those measured in our studied substrates. Rosas‐Castor et al (2014) observed As accumulation in maize ( Zea mays L.) when grown on a soil with an As concentration comparable with that in our substrates, but their recorded values in the shoot were mainly below our LQ for As (1.24 mg kg −1 , Supplemental Table S1).…”
Section: Resultscontrasting
confidence: 52%
“…The addition of phosphate increases soil permeability, thus contributing to arsenic migration deeper into the soil profile and entering groundwaters. This involves increasing its availability and uptake by plants (Scheckel et al 2013;McBride et al 2014;McBride et al 2015;Lim and McBride 2015).…”
Section: Soil Factors Affecting Metal Accumulationmentioning
confidence: 99%
“…Demethylation and methylation occurred because both inorganic arsenic species and DMA were also detected in the percolating water 70 . As with mining-impacted soils, plants grown on soils that are high in arsenic from arsenical pesticide contamination take up higher levels of arsenic into their edible tissues, observed for example in potatoes 71 , carrots 72 and leafy green vegetables 73, 74 .…”
Section: Anthropogenic Sources Of Arsenic To Soilmentioning
confidence: 99%